2017
DOI: 10.1080/01443615.2017.1328589
|View full text |Cite
|
Sign up to set email alerts
|

Increased C4d and Bb immunoreactivity and decreased MBL immunoreactivity characterise first-time pathologic first-trimester miscarriage: a case-control study

Abstract: The role of the complement system in first-time pathologic first-trimester miscarriage was investigated. In this case-control study, tissue samples of 126 women with pathologic miscarriage and termination of normal pregnancies were assessed. The pathologic pregnancy group consisted of 40 women with missed miscarriage, 13 women with incomplete miscarriage and 10 women with a blighted ovum. The control group consisted of 63 normal-appearing pregnancies. Immunoreactivity for C4d, Bb and MBL was evaluated in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…MBL seems to play different roles in various pregnancy pathologies. MBL deficiency increases the susceptibility to microbial infections, and it has been reported in first‐time miscarriage, 19 recurrent miscarriage, 20,21 preterm birth, premature rupture of membranes and histological chorioamnionitis, 21 and pre‐eclampsia 21,22 . In contrast, several studies report increased maternal serum levels of MBL in women with pre‐eclampsia and HELLP syndrome, 4,49 which is in agreement with studies describing an active pro‐inflammatory role of high serum MBL concentrations in chronic diseases, such hypoxia ⁄reperfusion injury and microvascular complications in diabetes 50‐53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MBL seems to play different roles in various pregnancy pathologies. MBL deficiency increases the susceptibility to microbial infections, and it has been reported in first‐time miscarriage, 19 recurrent miscarriage, 20,21 preterm birth, premature rupture of membranes and histological chorioamnionitis, 21 and pre‐eclampsia 21,22 . In contrast, several studies report increased maternal serum levels of MBL in women with pre‐eclampsia and HELLP syndrome, 4,49 which is in agreement with studies describing an active pro‐inflammatory role of high serum MBL concentrations in chronic diseases, such hypoxia ⁄reperfusion injury and microvascular complications in diabetes 50‐53 .…”
Section: Discussionmentioning
confidence: 99%
“…3 The interaction of EVTs with C1q is strongly inhibited by mannose-binding lectin (MBL), one of the factors increased in pre-eclamptic patient sera. 4 In addition, complement activation is required basis of their history of pregnancy complications, including control patients who had uncomplicated pregnancies and term deliveries (control, n = 33), and three groups of patients with a history of pregnancy complications, including preterm labour (n = 29), recurrent miscarriage (n = 19) or unexplained intrauterine foetal death (IUFD; n = 17). All women enrolled in the study had an interval of three to six months following their previous pregnancy, and they agreed to have a blood sample taken.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that trophoblast dysfunction, due to compromised trophoblast infiltration and apoptosis, as well as multiple aberrant signal transduction pathways (64), could lead to adverse pregnancy outcomes, including uRPL (65). In detail, all the impaired pathways previously investigated in RPL trophoblast cells functions (including kisspeptin/GPR54 and PIBF/PR pathways, C4d and Bb, MBL, NOD1 and NOD2 via MAPK/p38 pathway, miR-27a-3p/USP25 axis, Fas and FasL, PKC protein, CCNA2, TWIST, Prototype and Chimera-Type Galectins, miR-520 and PARP1, BMAL1 via SP1-DNMT1/DAB2IP pathway, EIF5A1 via ARAF-mediated activation of integrin/ERK signaling pathway, Stathmin-1, peroxiredoxin2are) are linked to trophoblast migration, proliferation, invasion and apoptosis processes potentially relevant for RPL pathogenesis (64,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Less is known about potential immunological impaired processes induced by trophoblast dysfunction.…”
Section: The Fetal-maternal Interfacementioning
confidence: 99%
“…However, it is not known whether these properties are maintained when using placental tissue from ongoing pregnancies, and whether the properties may be altered in a pathological condition. In uRPL, a compromised trophoblast function has been suggested, 7,8 mainly involving multiple aberrant signal transduction pathways, 7,[9][10][11][12][13][14][15][16][17][18][19][20][21] while their potential immunological dysfunction in uRPL has not been explored.…”
Section: Introductionmentioning
confidence: 99%